Psychological Symptoms of COVID-19 Pandemic Among Community-Dwelling Older People in Oman and Associated Risk Factors - Saleha Al-Jadidi MD; Maryam Alharrasi RN, PhD; Ahmed Al-Shukaili PhD; Ali Alkalbani RN; Akila Muthukrishnan RN, PhD (SAGE Publishing, 2024)
Introduction The COVID-19 pandemic has led to a dramatic loss of human lives worldwide. Objective This study aimed to investigate the psychological factors of the COVID-19 pandemic in the community-dwelling older population. Method This was a cross-sectional study of older people aged ≥60 years with no mental or psychological illnesses. A total of 193 participants were recruited. The study questionnaire included anxiety- and depression-related questions tailored for the COVID-19 pandemic. The questionnaire was developed through a literature review and expert review. Data was collected from December 2020 to January 2022. Results The psychological symptoms of COVID-19 were high in this sample (mean 29.18 ± 3.57). Gender (female) was found to have a strong positive relationship with the psychological symptoms of COVID-19 score ( p  = 0.003). Chronic illnesses (β = 0.19, p  < 0.001), living alone (β = 0.39, p  < 0.001), and having a family member or a friend with COVID-19 (β = 0.15, p  < 0.001) were also found to have a strong positive relationship with the psychological symptoms of COVID-19 score. Conclusion The negative psychological effects of COVID-19 were high among the older population in Oman. In this study, female gender, chronic illnesses, living alone, and having a family member or a friend with COVID-19 were associated with worse COVID-19 psychological symptoms. Older women were affected by COVID-19 more than older men. In addition, those who had chronic illnesses, lived alone, or had a family member or a friend with COVID-19 were more psychologically burdened by the pandemic than those without those characteristics. Particular attention should be given to older adults who have chronic illnesses, live alone, or have a family member or a friend with COVID-19. Support groups and psychological counseling programs are essential for older people during a pandemic.